LAPORAN LAPORAN KASUS: DEEP PYODERMA PADA KUCING MIX PERSIA UMUR 1 TAHUN - Lestari, Annisa Astuti; Putriningsih, Putu Ayu Sisyawati; Soma, I Gede (VITEK : Bidang Kedokteran Hewan, 2025)
Deep pyoderma is a bacterial skin infection that affects the dermis and subcutaneous tissue. A 1-year-old female Persian mix local breed cat presented with complaints of itching for 5 days, accompanied by frequent scratching. On physical examination, dry lesions and wet lesions were found in the form of ulcers in the mandibularis and cranial sinister extremities, and moist wounds in the mandibularis dexter area, as well as alopecia and debris in the mandibularis, cervicalis sinister et dexter, axilla dexter, and cranial sinister extremities. Hematology examination showed leukopenia, lymphocytosis, and granulocytopenia. Cytologic examination found cocci-shaped bacteria. Based on history taking, physical examination, and supporting examination, the cat was diagnosed with deep pyoderma. The treatment given was amoxycilline-clavulanic acid at a dose of 62.5 mg/cat q12h PO for 7 days, betamethasone-neomycin sulfate twice a day until the wound heals, dexamethasone injection at a dose of 0.07 mg/kg BW q24h IM and continued with the administration of methylprednisolone PO at a dose of 2 mg/cat q12h for 3 days, fish oil softcapsules once a day for 7 days besides being given chlorhexidine gluconate 4%. The results of 24 days of treatment showed that the cat's skin condition had improved.